Starting from the equation:
![E=(1)/(2)mv^2](https://img.qammunity.org/2023/formulas/physics/college/8mu31il3trth4pblkv7hi7l5xzubb6pk80.png)
Multiply both members by 2 to cancel out the factor of 1/2 on the right member of the equation:
![\begin{gathered} \Rightarrow2E=2((1)/(2)mv^2) \\ \Rightarrow2E=mv^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/og1nch3se6q1pswte5b8zctxtn6hpsgxj3.png)
Divide both members by m to cancel out the factor of m on the right member of the equation:
![\begin{gathered} \Rightarrow(2E)/(m)=(mv^2)/(m) \\ \Rightarrow(2E)/(m)=v^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/lci67ewxqoljz76s3flwjeh98g3e7uc6sr.png)
Take the square root of both member of the equation to get rid of the exponent of v:
![\begin{gathered} \Rightarrow\sqrt[]{(2E)/(m)}=\sqrt[]{v^2} \\ \Rightarrow\sqrt[]{(2E)/(m)}=v \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/ii6hrbfy19mhqjk6gr5emkk65copt3ts5m.png)
Therefore, the equation rearranged so that it is solved for v is:
![v=\sqrt[]{(2E)/(m)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/bq55vs7wgslsls3dblz9ktkxpasvex5wca.png)